2020
DOI: 10.1108/ijbm-04-2020-0210
|View full text |Cite
|
Sign up to set email alerts
|

Board gender diversity and environmental, social and governance performance of US banks: moderating role of environmental, social and corporate governance controversies

Abstract: PurposeGender diversity in corporate boards is broadly studied in existing corporate governance literature. However, the role of board gender diversity on environmental, social and governance (ESG) performance of the banks is still unaccounted for. Drawing on resource dependence and legitimacy theory, this study addresses this pressing research issue. Moreover, investigation of ESG controversies as a moderator paves the existing corporate governance research to the new avenues.Design/methodology/approachData w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 55 publications
3
66
0
1
Order By: Relevance
“…However, such contributions are scarce. Shakil et al [27] found a positive relationship between board gender diversity and CSR for a sample of 37 American banks between 2013 and 2017. García-Sánchez et al [78] confirmed this relationship for a sample of 159 banks in nine countries (seven European countries plus the United States and Canada) between 2004 and 2010.…”
Section: Csr and Gender Diversity: Analysis Of The Banking Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…However, such contributions are scarce. Shakil et al [27] found a positive relationship between board gender diversity and CSR for a sample of 37 American banks between 2013 and 2017. García-Sánchez et al [78] confirmed this relationship for a sample of 159 banks in nine countries (seven European countries plus the United States and Canada) between 2004 and 2010.…”
Section: Csr and Gender Diversity: Analysis Of The Banking Sectormentioning
confidence: 99%
“…Accordingly, the study of this relationship has scarcely covered the financial sector [26]. Therefore, there is a need for research to further explore the relationship between gender diversity and CSR in the banking sector [27]. Despite the scarcity of research on the banking industry, this sector is characterized by its prominent role in economic development [28], providing capital for innovation and infrastructure and creating jobs and general prosperity [29].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common criteria used to determine the extent of business disclosures is the company's size, where in this study, it refers to the bank's size. Larger company size is able to report more information about their investment in ESG as they have sufficient resources and facilities (Shakil et al, 2020). Gul and Leung (2004) and Luna Sotorrío and Fernández-Sánchez (2010) have also found a positive relationship between company size and voluntary information disclosure.…”
Section: Control Variablesmentioning
confidence: 95%
“…In other words, to know whether a company is formally and socially accountable to the community, it could be observed through a company's ESG score. Better ESG performance for a company reflects the company's social and environmental obligation, which provides more reliable information and stable stock price fluctuations in the market (Shakil et al, 2020). Companies with low minimum ESG performance are unstable in the market due to their irresponsible and unconcern nature.…”
Section: Introductionmentioning
confidence: 99%
“…Lo studio analizza anche l'effetto moderatore di fattori riconducibili alla teoria istituzionale: in particolare, la maggiore protezione degli investitori e un ambiente regolamentare più stringente amplificano l'effetto positivo esercitato dalla diversità di genere. Allo stesso modo, Shakil et al (2020) 114 identificano una relazione positiva tra la performance ESG delle banche e i direttori femmine in un campione di banche US nel periodo 2013-2017. La performance ESG è impattata diversamente nello studio di Al-Jaifi (2020) 115 : le donne nei board delle banche che hanno sede nell'ASEAN, investigate tra il 2011 e il 2016, non sembrano influenzare la performance sociale e ambientale, ma solo quella relativa alla corporate governance.…”
Section: La Retribuzione Collegata Alla Performance Esgunclassified